Maurice Sendak's seven little monsters : monsters in space - Yorinks, Arthur; Sendak, Maurice (New York : Volo/Hyperion Books for Children, 2003)
Seven members of a monster family take a trip into space.
Keywords: Monsters -- Fiction; Outer space -- Exploration -- Fiction